Decision support tools for agricultural adaptation in Africa - Rosenstock, Todd S; Joshi, Namita; Segnon, Alcade C; Cramer, Laura K.; Mwongera, Caroline; Nowak, Andreea C.; Njuguna, Lucy; Dossou-Yovo, Elliot R.; Steward, Peter; Ramirez-Villegas, Julian (Nature Portfolio, 2024)
Extensive and strategic investments are needed to adapt African agriculture to climate change. In 2020, US$2.8 billion were committed to adaptation in the agriculture, forestry and land use sector. This figure is likely to rise as the public and private sectors focus efforts on national commitments towards the Paris Agreement (the so-called Paris Alignment) and all African countries prioritize agricultural adaptation. Design of adaptation investments may be informed by the many web-based decision support tools (DSTs) available. Effective DSTs enable access to the latest science and data, potentially increasing the efficacy and impact of adaptation programming. However, the actual utility of DSTs remains a question.